Integrasi Linguistik dan Kajian Keagamaan: Peran Kajian Bahasa dalam Kajian KeIslaman - Saifuddin Ahmad Husin (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2022)
Knowledge integration has been studied as the process of incorporating new information into a body of existing knowledge with an interdisciplinary approach. Language is not only the object of the scientific study of linguistics but also the object of study of other related disciplines. The importance of language in many studies and disciplines of knowledge has led to its status as a condition sin qua non to a true understanding of other scientific objects of disciplines of knowledge. The mastery of the Arabic language for example is a must for the study of Islamic religious texts. The religion of Islam places language in a very high position that it is explicitly mentioned in the Qur’an as one of the signs of the existence of God. Keywords: Linguistics, language, Islam, Shari’ah.